?EVALUATION OF SOMACLONAL VARIANTS FOR YIELD AND SOME QUALITY PARAMETERS (Biological Sciences - PJSIR, 1999)
A field experiment was conducted to examine the variability of eight somaclones for agronomic and quality parameters. A significant reduction in plant height and days to tlowering was noted. There was increase in kernel length and head rice recovery.TF4 was selected having stiff stem, early in tlowering, semi dwarf with high fertility,bettergrain quality and greater yield potential than the parent variety. TF8, TF9 and SN12 yielded at par with the parentt variety i. e. Basmati 370, Profuse but unproductive tillers did not contribute to the yield. Linear relationship existed between in- creased UB ratio and better grain quality.The grains of all the somaclones were fine type, slender in shape and long in size..The highest quality Index was exhibited by TF9 followed by TF11 and TFIO respectively.